Hubungan Tingkat Pendidikan dan Sikap dengan Kepatuhan Minum Obat Pasien Tuberkulosis Paru: Relationship between Education Level and Attitude with Medication Adherence in Pulmonary Tuberculosis Patients - Puji Lestari; Feri Catur Yuliani; Dwi Puji Susanti (Universitas Ngudi Waluyo, 2026)
Pulmonary tuberculosis remains a health problem in Indonesia. The main obstacle to treating pulmonary tuberculosis is low patient adherence to taking medication regularly, which can lead to drug resistance and treatment failure. Patient adherence is influenced, among other factors, by education and attitude. The research aims to determine the relationship between education level and attitude with medication adherence in pulmonary TB patients who receive outpatient care at Pati Islamic Hospital. The research used an analytical quantitative design with a cross-sectional approach. The number of respondents is 40 patients, selected using purposive sampling. The research instruments were an education level questionnaire, a Guttman scale attitude questionnaire, and the MMAS-8 medication adherence scale. The research analysis was performed using the Spearman Rank test. The results showed that the majority of respondents had a secondary education level (35%) and moderate attitudes (60%). The most common level of adherence was moderate (52.5%). There was a significant relationship between education level and adherence (p = 0.000; ρ = 0.65) and between attitude and adherence (p = 0.000; ρ = 0.72). Conclusion of the study: The higher the level of education and positive attitude of patients, the higher the adherence to taking tuberculosis medication.